Sensitivity of human lymphocytes to genotoxic effect of N-methyl-N-nitrosourea: possible relation to gynecological cancers - Tronov, V.A.; Kramarenko, I.I.; Kozlova, A.D.; Dederer, L.J.; Kedrova, A.G.; Gorbacheva, L.B. (Інститут експериментальної патології, онкології і радіобіології ім. Р.Є. Кавецького НАН України, 2006)
The aim of this work is to study responses of PHA-stimulated and resting lymphocytes to methylating agent N-methyl-N-nitrosourea (MNU) and to compare sensitivity to this agent of healthy donor lymphocytes and lymphocytes from patients with gynecological cancers. Methods: Cytotoxicity of MNU, apoptotic death of lymphocytes, was evaluated using two common tests – annexin V-FITC detection assay and live/dead double staining assay (nuclear morphological changes). Genotoxic effect of the agent was determined as delayed (secondary) DNA double strand breaks (DSBs) using neutral comet assay both conventional variant and modified for detection of bromodeoxyuridine-labelled comets, produced by proliferating lymphocytes only. Results: Unstimulated lymphocytes were tolerant to geno- and cytotoxic effects of MNU. In contrast to resting cells, proliferating lymphocytes showed significant genotoxicity (p = 0.0054) of MNU followed by increased apoptotic death of cells (p < 0.05). Average number of secondary DSBs induced by MNU in lymphocytes from patients with gynecological cancers was about 4-fold less than that of lymphocytes of healthy donors. While lymphocytes from cancer patients did not change proliferative index in response to MNU, the agent decreased 2-fold proliferative indices of stimulated lymphocytes from healthy donors. Conclusion: There is a reverse association between geno- and cytotoxicity of MNU in stimulated lymphocytes and the presence of tumor. The relationship appears to be based on MMR-insufficiency in lymphocytes of the cancer patients. Цель: исследование эффекта метилнитрозомочевины (МНМ) на ФГА-стимулированные лимфоциты и в состоянии
покоя здоровых доноров и пациенток с опухолями женской половой сферы. Методы: цитотоксический эффект МНМ
(апоптотическая гибель лимфоцитов) оценивали по двум показателям — взаимодействию клеток с комплексом annexin
V-FITC и по морфологическим изменениям ядра клеток после их окрашивания смесью 2 ДНК-тропных красителей.
Генотоксический эффект МНМ, вторичные двунитевые разрывы ДНК (ДР) определяли с помощью метода нейтральных
ДНК-комет. Использовали стандартный вариант метода и модифицированный для подсчета комет, формируемых только
делящимися лимфоцитами, меченными BrUdr. Долю таких комет представляли как индекс пролиферации клеток. Результаты:
лимфоциты в состоянии покоя устойчивы к гено- и цитотоксическому эффектам МНМ. В пролиферирующих клетках в ответ
на воздействие МНМ формировались вторичные разрывы ДНК (р < 0,01) и возрастала частота появления апоптотических
клеток (р < 0,05). Генотоксический эффект МНМ на стимулированные лимфоциты больных онкологического профиля в
4 раза ниже, чем на лимфоцитах здоровых доноров. Лимфоциты пациенток не изменяли пролиферативный индекс в ответ на
действие МНМ; в лимфоцитах здоровых доноров действие МНМ вызывало 2-кратное снижение пролиферативного индекса.
Выводы: установлена связь между гено- и цитотоксическим ответом лимфоцитов на действие МНМ и наличием опухоли.
Предполагается, что генотоксический эффект МНМ связан с процессом пострепликативной коррекционной репарации.